Acremonium species skin infection in a female French bulldog - Vladislav E Sobolev (International Journal of Veterinary Science and Research - Peertechz Publications, 2022)
Currently, the role of opportunistic pathogenic microflora in the total number of dermatological patients in veterinary clinics has increased significantly. As the author's personal experience shows, the clinical significance of fungal opportunistic microflora is often underestimated by veterinary professionals. The article considers a case of successful treatment of Acremonium spp skin infection in an 11-year-old female French bulldog. A course of therapy using itraconazole, terbinafine, probiotics, and topical treatment of the skin with an aerosol product containing 8-oxyquinoline (C9H7NO) stopped the infection within 8 weeks. A follow-up examination of the dog after 3 months showed 90% hair regrowth and no evidence of infection.